Spiritual Activism. Saving Mother Earth in Sápmi - Kraft, Siv Ellen (Religions, 2020)
Arctic Shaman Circle was founded in Oslo in November 2018. This article discusses what the Circle’s founding document refers to as “spiritual activism”, and how this was translated into action over the year that followed. I will follow one case in particular, which concerns plans for a power plant at the base of the mountain Aahkansnjurhtjie in the South Sámi area. Aahkansnjurhtjie is a sacred Sámi mountain, the shamans claim, and should be protected accordingly. My focus is on the learning processes that have emerged as the shamans have explored and argued the case, locally and nationally. I examine the negotiations that have happened along the way, in a political climate that has so far been hostile to religious arguments of any sorts, and in this example, involves a group that is contested among the Sámi. Finally, I look at the role of “indigeneity” in regard to claims, performances and responses to these particular concerns, as these have played out in different parts of the Sámi geography.